Soil quality of degraded land of Bundelkhand region with special reference to Jhansi district of Uttar Pradesh - Rajdeep Kudesia, Kiran, Amit Pal, (Journal of Phytology, 2009)
Present study has been taken to assess the quality of soil in and around Jhansi district of Bundelkhand region of Uttar Pradesh which is also known as ecologically fragile ecosystem. For the present investigation fifteen villages have been selected randomly. Majority of the soil in this area has been found in less nutritive value and not suitable for proper agricultural activities. Results show that pH of the soils varies 6.8 to 8.4; OC 0.07 to 0.78%; and N 0.01 to 0.13% respectively. Available P, K as well as micronutrients viz. Cu, Fe, Mn, Zn are also found less than standard as prescribed by Indian Council of Agricultural Research, New Delhi and not in suitable for agricultural crops. Ã‚Â